2019
DOI: 10.15829/1560-4071-2019-4-78-82
|View full text |Cite
|
Sign up to set email alerts
|

Effects of benfotiamine on the insulin resistance state, some pro- and anti-inflammatory factors content in patients with type 2 diabetes mellitus and cardiac autonomic neuropathy

Abstract: Цель. Проанализировать влияние бенфотиамина (БФТ) на состояние инсулиновой резистентности, содержание некоторых про-и противовоспалительных факторов у пациентов с диабетом 2 типа (СД2) и клинической стадией кардиальной автономной нейропатии (КАН). Материал и методы. Обследовано 40 пациентов с СД2 и клинической стадией КАН, возраст 50-59 лет, с длительностью заболевания 1-6 лет с медианой уровня гликированного гемоглобина (HbA 1c) 7,16%±0,19%. Пациенты были разделены на 2 группы. Пациенты первой группы получали… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This might improve the growth performance of fish. Additionally, benfotiamine administration has been demonstrated to reduce hyperglycaemia‐induced the metabolic damages in mammals by the inhibition of inflammation (Hammes et al, 2003; Serhiyenko et al, 2019). It is possible that a similar mechanism also exists in fish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might improve the growth performance of fish. Additionally, benfotiamine administration has been demonstrated to reduce hyperglycaemia‐induced the metabolic damages in mammals by the inhibition of inflammation (Hammes et al, 2003; Serhiyenko et al, 2019). It is possible that a similar mechanism also exists in fish.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it also has potent antioxidant, anti‐inflammatory, anti‐apoptotic and anti‐carcinogenic properties (Beltramo et al, 2008; Tapias et al, 2018). In the study of diabetes, benfotiamine has been shown to prevent β‐cell dysfunction by inhibiting inflammation, thereby improving insulin resistance in tissues (Serhiyenko et al, 2019). However, literature regarding the influences of this substance on aquatic animals is extremely scarce.…”
Section: Introductionmentioning
confidence: 99%
“…This might improves the growth performance of sh. Additionally, benfotiamine administration has been demonstrated to reduce the metabolic damage induced by hyperglycemia in mammals by the inhibition of in ammation, and the decrease of advanced glycation end products (AGEs) formation [24,27]. This is possible that a similar mechanism exists in sh.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it also has potent anti-oxidant, anti-in ammatory, anti-apoptotic and anti-carcinogenic properties [25,26]. In the study of diabetes, benfotiamine has been shown to prevent β-cell dysfunction by inhibiting in ammation, thereby improving insulin resistance in tissues [27]. However, information regarding the effects of this substance on aquatic animals is extremely scarce.…”
Section: Introductionmentioning
confidence: 99%